Normal Serum Levels of Otolin-1 in Patients with Meniere Disease in Remission - Singh, Anup; Yadav, Harsha; Verma, Hitesh; Sikka, Kapil; Abraham, Ransi Ann; Irugu, David Victor Kumar (International Archives of Otorhinolaryngology, 2023)
Introduction Degenerative changes in the otolithic organs have been theorized to be caused by the mechanical obstruction to endolymphatic flow, possibly resulting in endolymphatic hydrops (ELH). Otolin-1 is an otoconial matrix protein that crosses the blood labyrinth barrier and has been found in the serum of healthy and diseased patients.Objective To measure the serum levels of Otolin-1 in Meniere disease (MD) patients and compared them with the healthy individuals.Methods This pilot, cross-sectional study was performed at our tertiary care referral center to compare the serum Otolin-1 levels of healthy individuals with those of MD patients. The blood samples were obtained during patients' visit to the vertigo clinic following remission of an acute episode. The data was analyzed using the Stata/SE version 12.0 (StataCorp. College Station, TX, USA). Comparison between the serum Otolin-1 levels in the two groups was performed using the unpaired t-test. A p-value of 0.05 was considered to be statistically significant.Results The participants were divided into two groups, with 31 MD patients, and 30 age and gender-matched members of the control group. The serum levels of Otolin-1 in MD patients (247.6, ± 44.2 pg/ml) were not found to be significantly different from those of the control group (236.2, ± 43.5 pg/ml) (p = 0.31).Conclusion The current study reveals that the serum levels of Otolin-1 are not significantly different between the patients with MD in the interictal phase and the control group's healthy ones.
Keywords: Meniere disease; otolithic membrane; endolymph drainage; biomarkers